KEDUDUKAN DAN TANGGUNG JAWAB PENJAMIN DALAM BORGTOCHT: TINJAUAN ATAS PERLINDUNGAN HUKUM BAGI PIHAK KETIGA - Septiaji, Satriya Ardhi Dwi; Ar-Rosyida, Haizah; Alifah, Wardiati; Musadad, Ahmad (Jurnal Ilmiah Advokasi, 2025)
Borgtocht or debt guarantee agreement is a form of personal guarantee that is accessory, as regulated in Articles 1820-1850 of the Civil Code. This study aims to analyze the legal position of the insurer and legal protection for third parties in the context of borgtocht agreements, especially in banking practices in Indonesia. The method used is a normative and comparative juridical approach with the Dutch legal system, where two forms of borgtocht are known: simple and solidarity. This study found that although borgtocht provides protection to creditors, its implementation still faces legal obstacles, especially in the condition of a bankrupt debtor. Legal protections for insurers such as subrogation rights and the principle of subsidiarity are often overlooked in practice. In the context of third parties, both the insurer's heirs, other creditors, and parties with an interest in the insurer's assets, the existing regulations do not provide adequate legal certainty. Therefore, regulatory reform and affirmation of agreement clauses are needed so that borgtocht can be implemented fairly and effectively.Keywords: borgtocht, insurer, third party, accessoir agreement, legal protection